Hereditary Hemorrhagic Telangiectasia in a Sudanese Patient - Omer Ali Mohamed Ahmed Elawad; Ahmed Abdalazim Dafallah Albashir; Mohammed Mahgoub Mirghani Ahmed; Ahmed Ali Mohamed Ahmed Elawad; Osman Eltieb Elbasheer Mohamed (Case Reports in Medicine)
Background. Hereditary hemorrhagic telangiectasia (HHT) also known as Osler–Weber–Rendu syndrome is a rare autosomal dominant disorder, which results in vascular dysplasia affecting mainly visceral and mucocutaneous organs. Case Presentation. A 65-year-old woman with a 12-year history of recurrent spontaneous epistaxis presented with shortness of breath, easy fatigability, and bilateral lower limb edema. Her family history was significant for definite hereditary hemorrhagic telangiectasia in first-degree relatives. During the previous 15 days, she has experienced three episodes of recurrent nasal bleeding. She has a background of chronic mitral regurgitation. Physical examination revealed telangiectases in her tongue, lower lip, and hand in addition to signs of congestive heart failure. The patient met 3\4 Curacao criteria and had a definite HHT. Her laboratory workup revealed a hemoglobin count of 5.4 g/dl. Echocardiography revealed a left systolic ejection fraction of 51% with left atrial dilatation and severe mitral regurgitation. Chest X-ray showed features of cardiomegaly and pulmonary edema. The abdominal ultrasonography showed enlarged liver size with homogenous texture and congested hepatic veins without features of hepatic AVMs. She was treated with intravenous frusemide, iron supplement, tranexamic acid, blood transfusion, and nasal packing. Conclusions. HTT usually passes unnoticed in Sudan. The rarity of HHT, difficulties in affording diagnostic imaging studies, and low clinical suspicion among doctors are important contributing factors. Anemia resulting from recurrent epistaxis might have an influential role in precipitating acute heart failure in those with chronic rheumatic valvular disease.